DESAIN SISTEM PROPULSI HYBRID PADA FAST PATROL BOAT 28 METER - Muhammad Septaldi Millenian S; Raden Dimas Endro W; Anggara Trisna Nugraha (Proceedings Conference on Marine Engineering and its Application, 2023)
Hybrid System Vessel technology has recently become a frequently discussed topic in machinery technology. The Hybrid System Vessel technology in question is a ship that runs with two power sources, an engine that works with a fuel power source and an electric motor that works with an electric power source. The object of this research is a 28 m Patrol Ship with a speed of 25 knots in full conditions (MCR), 22 knots in Patrol conditions and 15 knots in economic conditions. The electric motor used is the PRAXIS DC EMG590d-620 motor with a power of 584 kW supplying motor power from the battery and the diesel motor used is the Baudoin M126.3 motor with a power of 1104 Kw. Simulation using MatLab by modeling the motor and propeller to find the value of torque, thrust and speed advance. Obtained power prediction DC motor, motor speed can meet the needs of the desired economic speed of 16.78 kNot, obtained power prediction Diesel Motor, motor speed can meet the needs of the desired patrol speed of 22.17 kNot